Diluted povidone-iodine versus saline for dressing metal-skin interfaces in external fixation - Chan, C.K.; Saw, A.; Kwan, M.K.; Karina, R. (2009)
PURPOSE: To compare infection rates associated with 2 dressing solutions for metal-skin interfaces. METHODS: 60 patients who underwent distraction osteogenesis with external fixators were equally randomised into 2 dressing solution groups (diluted povidone-iodine vs. saline). Fixations were attained using either rigid stainless steel 5-mm diameter half pins or smooth stainless steel 1.8-mm diameter wires. Half-pin fixation had one metal-skin interface, whereas wire fixation had 2 interfaces. Patients were followed up every 2 weeks for 6 months. RESULTS: Of all 788 metal-skin interfaces, 143 (18) were infected: 72 (19) of 371 in the diluted povidone-iodine group and 71 (17) of 417 in the saline group. Dressing solution and patient age did not significantly affect infection rates. Half-pin fixation was more likely to become infected than wire fixation (25 vs 15). CONCLUSION: Saline is as effective as diluted povidone-iodine as a dressing solution for metal-skin interfaces of external fixators. Saline is recommended in view of its easy availability and lower costs.